2008
DOI: 10.2174/1874120700802010036
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Assisted Decontamination of Bacterial Spores

Abstract: The efficacy and mechanism of killing bacterial spores by a plasma torch is studied. Bacterial-spore (Bacillus cereus) suspension is inoculated onto glass/paper slide-coupons and desiccated into dry samples, and inoculated into well-microplate as wet sample. The exposure distance of all samples is 4 cm from the nozzle of the torch. In the experiment, paper slide-coupon is inserted inside an envelope. The kill times on spores in three types of samples are measured to be about 3, 9, and 24 seconds. The changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The presence of water appeared to enhance the efficacy of the NTP‐AA treatment, although another study reported that it was much slower to kill wet spores suspended in water than dry ones on a glass slide with a microwave‐powered air NTP torch because excessive water formed a barrier preventing reactive oxygen species from reaching the spores . No survival was observed for NTP‐treated wet samples of BA spores by plating on nutrient media at even the shortest NTP treatment time of 1 min (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The presence of water appeared to enhance the efficacy of the NTP‐AA treatment, although another study reported that it was much slower to kill wet spores suspended in water than dry ones on a glass slide with a microwave‐powered air NTP torch because excessive water formed a barrier preventing reactive oxygen species from reaching the spores . No survival was observed for NTP‐treated wet samples of BA spores by plating on nutrient media at even the shortest NTP treatment time of 1 min (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Many factors affect the mechanisms of spore inactivation by NTP, even within a narrower domain of non‐thermal atmospheric pressure plasma, making pinpointing the inactivation mechanisms difficult and sometimes controversial. In a study using microwave‐powered air NTP torch, fast inactivation rate (6‐log 10 reduction in ∼17 s) of Bacillus cereus spores was reported, and the NTP torch was able to kill spores inside an paper envelope at a slower rate without damaging the envelope. Effective inactivation of Bacillus spores using atmospheric DBD plasma was also reported .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the oxidation process, chemically reactive oxygen species (ROS) are known to be effective in the disruption of the bacterial cell wall [11][12][13]. The role of oxygen radicals in plasma sterilization has been also demonstrated: the rate of bacterial inactivation in the oxygen plasma group was greater than that in the helium plasma group.…”
Section: The Efficacy Of Cap In Biosciencementioning
confidence: 99%